PROGRAM PLANNING AND CONTROL THROUGH THE BUDGETARY PROCESS. - Harton, William R. (The Accounting Review, 1954)
Abstract The article focuses on program planning and control through the budgetary process. The budget is an instrument which should guide the executive in planning and controlling the operations of the company, but it should never dictate the policies of the management. When properly prepared and executed, the budget document can, with a reasonable degree of accuracy, forecast the results of a proposed program before it is inaugurated. The budget in government is a financial plan for raising and spending money to conduct operations and to meet outstanding obligations. A distinction is made in public finance between annual or operating budgets, and long-term or capital budgets. The operating budget provides a plan and funds for the day to day operations of government while the capital budget concerns itself with new construction of major installations involving long-term financing. All too often budgeting has been based on the premise that the budget should be only a financial statement and a request for funds.